The construal of requests for action: Expounding indeterminancy for socio-communicative risks and failures in public health. Issue 3 (2nd July 2020) - Ng, Anthony
Abstract : Requests for action are significant for ensuring clear communication and, delivering quality and safe services in health care but, if presented unclearly or implicitly, may cause indeterminacy, leading to socio-communicative risks and failures (Matthiessen, Christian M. I. M. 2013. Applying systemic functional linguistics in healthcare contexts. Text & Talk 33(4–5). 437–67). This research adopted an ideational approach (construing each process as a quantum of change in our experience), rather than the common interpersonal approach (enacting healthcare provider-patient interactions during the patient journey), examining healthcare communication as instances of exchange of social meanings in a semiotic system according to institutional roles, accountabilities, counterparty risks and power differentials (Halliday, Michael A. K. 1978. Language as social semiotic: The social interpretation of language and meaning . London: Edward Arnold; Halliday, Michael A. K. 1984a. Language as code and language as behaviour: a systemic- functional interpretation of the nature and ontogenesis of dialogue. In Michael A. K. Halliday, Robin Fawcett, Sydney M. Lamb, and Adam Makkai (eds.), The semiotics of language and culture . London: Frances Pinter; Halliday, Michael A. K. 1984b. Linguistics in the university: the question of social accountability. In James E. Copeland (ed.), New directions in linguistics and semiotics, 51–67. Houston, TX: Rice University Studies). 1, 206 instances of construals (processes) were quantitatively and qualitatively examined as "requests for action" or "references of information" in government "health advice letters" to education institutions in Hong Kong, drawing upon resources of Systemic Functional Linguistics (Michael A. K. Halliday, and Christian I. M. Matthiessen 2014. Halliday's Introduction to Functional Grammar, 4th ed. London: Routledge) and Critical Consciousness (Freire, Paulo. 1973. Education for critical consciousness . New York: Seabury). Although a significant 6% of these processes displayed indeterminate tendency in this pre-hospitalization context, the registerial profiling of requests (Action Orientation) contributes to (a) better expounding indeterminacy for further discussions on socio-communicative risks and failures, and (b) constructing an effective framework for analyzing discourses and navigating through various registers of health care in terms of socio-semiotic orientations and power differentials.